The Basic Chemistry Knowledge Effect on Students’ Achievement Through the Pathways in Tadulako University - Suheria Suheria; Sitti Nuryanti; Afadil Afadil (Jurnal Akademika Kimia, 2024)
This research aimed to analyse the influence of basic chemistry on the achievement (IP) of chemistry students (PSPK) at Tadulako University. The population of this research comprised all students of PSPK FKIP Tadulako University in the 2018/2019 academic year, totaling 464 students. The sampling technique used a stratified sample. The sample of this research was 115 students. The data for this research were obtained from the BAKP Tadulako University Archive, Tadulako University, and a questionnaire. The result of this research shows that basic chemistry has a positive influence on PSPK students’ IP through SNMPTN, with a coefficient of 0.032, a regression equation b = 3.281, t(23) = 0.067, and p < .692. through  SBMPTN by  0.877 with the equation regression b= 0.790, t(69) = 0.803, p > .000 and  SMMPTN by 0.843with the equation regression b=0.574, t(20) = 0.996, p > .000.